ADULT ATTACHMENT AND THE PERCEPTION OF OTHERS - Yárnoz Yaben, Sagrario; Alonso-Arbiol, Itziar; Plazaola, Mikel; Sainz de Murieta, Luis María (Anales de Psicología / Annals of Psychology, 2001)
The relationship between individuals’ attachment style and their perceptions of self andothers was examined in a sample composed of 118 female college students. To measure the identification differences, distances among the elements in the Kelly’s grid technique (self, mother, father, friends, partner, ideal self and ideal others) were used. As predicted, and with the only exception of the fearful attachment style, participants identified better with mothers’ characteristics than fathers’ ones. Furthermore, identification with peer’s characteristics was the more salient, only comparable to the identification with mothers’ characteristics, suggesting the transfer of peers as attachment figures in young adulthood. Data obtained for the comparison of attachment styles with the model of the self and the model of others did not confirm nor discard Bartholomew and Horowitz’s model. Results and future directions are discussed.